The Wnt Blows: On the Functional Role of Wnt Signaling in Mycobacterium tuberculosis Infection and Beyond - Brandenburg, Julius; Reiling, Norbert (Frontiers in Immunology, 2016)
In recent years, it has become apparent that the Wnt signaling pathway, known for its essential functions in embryonic development and tissue homeostasis, exerts immunomodulatory functions during inflammation and infection. Most functional studies indicate that Wnt5a exerts pro-inflammatory functions on its cellular targets, which include various types of immune and non-immune cells. Wnt5a expression has also been linked to the pathogenesis of chronic inflammatory diseases. Activation of beta-catenin-dependent Wnt signaling, e.g., by Wnt3a, has however been shown to limit inflammation by interfering with the nuclear factor kappa-light chain-enhancer of activated B-cells (NF-kappaB) pathway. This review focuses on the regulation of Wnt5a, Wnt3a, and the recently identified Wnt6 and their functional role in bacterial infections with a primary focus on pulmonary tuberculosis, a leading infectious cause of morbidity and mortality worldwide.